The surgeon’s role in transcatheter aortic valve implantation (TAVI) - Van Linden, Arnaud; Blumenstein, Johannes; Walther, Thomas; Kempfert, Joerg (SA Heart Journal, 2017)
Transcatheter aortic valve implantation (TAVI) has evolved into a routine procedure for elderly high-risk patients with severe aortic stenosis in specialised centres. It can be performed via a transfemoral or a transapical approach. Both approaches are truly minimally invasive and avoid the use of cardio-pulmonary bypass and cardioplegic arrest. TAVI is associated with good outcome and acceptable complication rates. The outcome of TAVI has improved over the last few years as centres became more experienced in the procedure. Up to now there is no clear evidence-based benefit for one or the other approach. A careful patient selection for each approach is therefore crucial for good results. Both procedures should be performed by a heart team of cardiologists, cardiac surgeons and cardiac anaesthetists. The knowledge the cardiac surgeons gained over the last decades by treating aortic stenosis with conventional aortic valve replacement is very important in TAVI procedures: Not only in terms of the procedure itself, but also for preoperative patient screening. TAVI must be approached as a team effort where cardiologists and cardiac surgeons play an equal role and should not be performed without a cardiac surgeon.